Lower urinary tract dysfunction in adult patients with mitochondrial disease. Issue 8 (24th September 2020) - Feeney, Catherine; Gorman, Grainne; Stefanetti, Renae; McFarland, Robert; Turnbull, Doug; Harding, Christopher; Sachdeva, Ashwin
Abstract: Aims: Mitochondrial diseases present with a spectrum of clinical features, usually with multiorgan involvement and are often characterized by a loss of smooth muscle function. Hence, we hypothesized that mitochondrial dysfunction may contribute to lower urinary tract (LUT) dysfunction. Methods: We performed a prospective cohort study at a single, quaternary, mitochondrial disease referral center, enrolling consecutive adult patients with genetically confirmed mitochondrial disease. Data regarding baseline characteristics and disease burden were gathered. LUT dysfunction was assessed using the International Consultation on Incontinence Modular Questionnaire‐Lower Urinary Tract Symptoms (ICIQ‐LUTS) questionnaire, bladder voiding efficiency (BVE), and bladder diaries. Patients with one or more features of LUT dysfunction were offered urodynamic testing. Results: A total of 109 patients were included. Twenty‐six percent of patients manifested at least one feature of LUT dysfunction, which was objectively confirmed in all 14 patients who consented to urodynamic investigation. Disease burden, defined by the Newcastle Mitochondrial Disease Adult Scale (NMDAS), demonstrated a linear relationship with ICIQ‐LUTS severity ( P = .01), with a statistically significant relationship between NMDAS‐gastrointestinal scores and LUTS scores ( P < .001). Limitations include mutational heterogeneity across the patient cohort. Conclusions: This is the largest study exploring LUT in patients with mitochondrial disease and supports previous smaller studies suggesting LUT dysfunction is underrecognized in patients with mitochondrial disease and impacts considerably on their quality of life. We propose a clinical guideline for identifying mitochondrial disease patients at risk of LUT dysfunction.